2020
DOI: 10.3389/fimmu.2020.00860
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Sex Affect the Immune Responses to Tick-Borne Encephalitis Booster Vaccination

Abstract: Obesity has dramatically increased over the last 30 years and reaches according to World Health Organization dimensions of a global epidemic. The obesity-associated chronic low-level inflammation contributes to severe comorbidities and directly affects many immune cells leading to immune dysfunction and increased susceptibility to infections. Thus, prophylaxis against vaccine-preventable diseases is crucial, yet the responsiveness to several vaccines is unclear under obesity. In order to assess the responsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…Similar to previous studies [ 21 , 22 ], we found that smoking and comorbidities e.g., DM and obesity were significantly associated with bacterial meningitis. Tobacco smoke exposure increases the risk of meningococcal disease however obesity and diabetics raise the risk of pneumococcal meningitis [ 21 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [ 21 , 22 ], we found that smoking and comorbidities e.g., DM and obesity were significantly associated with bacterial meningitis. Tobacco smoke exposure increases the risk of meningococcal disease however obesity and diabetics raise the risk of pneumococcal meningitis [ 21 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Depletion of Tregs is a useful approach to enable anti-tumor immunity as has been shown in melanoma patients, where administration of anti-CTLA4 mAbs not only activated T cells, but also depleted Tregs in tumor tissues (41). Previously, vaccination in healthy subjects and also in patients in our previous cancer trial led to relative reduction of Tregs in peripheral blood due to expansion of T effector populations (10,16,19,42); as such, this effect might be a further benefit of the active immunization approach in cancer treatment.…”
Section: Discussionmentioning
confidence: 92%
“…This reduction is attributed to the fact that HCD enhances PD-L1-mediated suppression of Tfh cell differentiation and immune response [ 47 ]. Another study did not observe a significant difference in the proportion of Tfh cells between obese and healthy mice, but it showed that obese mice had more IL-17 + Tfh cells and less IFN- γ + Tfh cells [ 48 ].…”
Section: Cholesterol In Cd4 + T Cellsmentioning
confidence: 99%